Serum and intestinal secretory IgA in alcoholic cirrhosis of the liver. Issue 6 (June 1982) - Pelletier, G; Briantais, M J; Buffet, C; Pillot, J; Etienne, J P
Abstract : Serum and intestinal secretory IgA (sIgA) were investigated in control subjects and patients with alcoholic cirrhosis of the liver. Intestinal secretions were sampled by intraluminal perfusion with a balloon catheter. Monomeric IgA and sIgA were assayed by reversed radial immunodiffusion and nephelometry after separation by Ultrogel column filtration. High levels of serum sIgA were found only in patients with severe cirrhosis accompanied by jaundice. The intestinal rate of secretion of sIgA measured in these patients was significantly lower than that observed in either controls or the patients with compensated cirrhosis. Such an intestinal sIgA deficiency, which could be explained either by a fall in small intestinal immunocyte synthesis or by a defect in the transenterocyte transport system, could be partially responsible for the high incidence of intestinal infection observed in severe cirrhosis.